Overcoming the egress block of Plasmodium sporozoites expressing fluorescently tagged circumsporozoite protein - Thieleke-Matos, Carolina; Walz, Kevin; Frischknecht, Friedrich; Singer, Mirko (Molecular microbiology, 2024)
Plasmodium sporozoites are the highly motile and invasive forms of the malaria parasite transmitted by mosquitoes. Sporozoites form within oocysts at the midgut wall of the mosquito, egress from oocysts and enter salivary glands prior to transmission. The GPI-anchored major surface protein, the circumsporozoite protein (CSP) is important for Plasmodium sporozoite formation, egress, migration and invasion. To visualize CSP, we previously generated full-length versions of CSP internally tagged with the green fluorescent protein, GFP. However, while these allowed for imaging of sporogony in oocysts, sporozoites failed to egress. Here, we explore different strategies to overcome this block in egress and obtain salivary gland resident sporozoites that express CSP-GFP. Replacing the N-terminal and repeat region with GFP did not allow sporozoite formation. Lowering expression of CSP-GFP at the endogenous locus allowed sporozoite formation but did not overcome egress block. Crossing of CSP-GFP expressing parasites that are blocked in egress with wild-type parasites yielded a small fraction of parasites that entered salivary glands and expressed various levels of CSP-GFP. Expressing CSP-GFP constructs from a silent chromosome region from promoters that are active only post salivary gland invasion yielded normal numbers of fluorescent salivary gland sporozoites, albeit with low levels of fluorescence. We also show that lowering CSP expression by 50% allowed egress from oocysts but not salivary gland entry. In conclusion, Plasmodium berghei parasites with normal CSP expression tolerate a certain level of CSP-GFP without disruption of oocyst egress and salivary gland invasion.